The bacteriology of pleural infection (TORPIDS): an exploratory metagenomics analysis through next generation sequencing - Kanellakis, NI; Wrightson, JM; Gerry, S; Ilott, N; Corcoran, JP; Bedawi, EO; Asciak, R; Nezhentsev, A; Sundaralingam, A; Hallifax, RJ; Economides, GM; Bland, LR; et al. (Elsevier, 2022)
Background Pleural infection is a common and severe disease with high morbidity and mortality worldwide. The knowledge of pleural infection bacteriology remains incomplete, as pathogen detection methods based on culture have insufficient sensitivity and are biased to selected microbes. We designed a study with the aim to discover and investigate the total microbiome of pleural infection and assess the correlation between bacterial patterns and 1-year survival of patients. Methods We assessed 243 pleural fluid samples from the PILOT study, a prospective observational study on pleural infection, with 16S rRNA next generation sequencing. 20 pleural fluid samples from patients with pleural effusion due to a non-infectious cause and ten PCR-grade water samples were used as controls. Downstream analysis was done with the DADA2 pipeline. We applied multivariate Cox regression analyses to investigate the association between bacterial patterns and 1-year survival of patients with pleural infection. Findings Pleural infection was predominately polymicrobial (192 [79%] of 243 samples), with diverse bacterial frequencies observed in monomicrobial and polymicrobial disease and in both community-acquired and hospital-acquired infection. Mixed anaerobes and other Gram-negative bacteria predominated in community-acquired polymicrobial infection whereas Streptococcus pneumoniae prevailed in monomicrobial cases. The presence of anaerobes (hazard ratio 0·46, 95% CI 0·24–0·86, p=0·015) or bacteria of the Streptococcus anginosus group (0·43, 0·19–0·97, p=0·043) was associated with better patient survival, whereas the presence (5·80, 2·37–14·21, p<0·0001) or dominance (3·97, 1·20–13·08, p=0·024) of Staphylococcus aureus was linked with lower survival. Moreover, dominance of Enterobacteriaceae was associated with higher risk of death (2·26, 1·03–4·93, p=0·041). Interpretation Pleural infection is a predominantly polymicrobial infection, explaining the requirement for broad spectrum antibiotic cover in most individuals. High mortality infection associated with S aureus and Enterobacteriaceae favours more aggressive, with a narrower spectrum, antibiotic strategies. Funding UK Medical Research Council, National Institute for Health Research Oxford Biomedical Research Centre, Wellcome Trust, Oxfordshire Health Services Research Committee, Chinese Academy of Medical Sciences, and John Fell Fund.